Meatball properties as affected by substitution of tapioca with purple sweet potato - H. Hajrawati; F. Maruddin; M. R. Hakim; Yu. Yulianti; A. N. M. Rasak; S. Suharyanto (Теория и практика переработки мяса, 2025)
This research investigated the effects of substituting tapioca flour with purple sweet potato flour (PSPF) on the physicochemical properties, antioxidant activity, and microstructure of chicken meatballs during cold storage. Purple sweet potato is rich in anthocyanins, which act as natural antioxidants and colorants, potentially enhancing the functional properties of meat products. Chicken meatballs were formulated with different levels of PSPF substitution (0%, 5%, 10%, and 15%) and evaluated for cooking loss, water holding capacity (WHC), gel strength, pH, color, total anthocyanin content, lipid oxidation, and scavenging activity over 15 days at 4 °C. Results showed that PSPF substitution significantly influenced cooking loss, WHC, gel strength, and color. The addition of PSPF increased total anthocyanin content and antioxidant activity, contributing to enhanced oxidative stability by inhibiting lipid oxidation. Microstructural analysis revealed that PSPF substitution led to a more homogeneous and compact matrix, reducing the porous nature of the meatballs. However, excessive substitution (≥10%) resulted in a decline in WHC and gel strength. The findings suggest that incorporating PSPF in chicken meatballs at a substitution level of up to 10% improves antioxidant properties while maintaining acceptable texture and physicochemical characteristics. This approach could serve as a natural alternative to synthetic antioxidants like butylated hydroxytoluene (BHT), aligning with the growing demand for healthier and functional meat products.